KONSEP PENDIDIKAN AKHLAK DALAM KITAB TA’LIM MUTA’ALLIM AZ-ZARNUJI DAN RELEVANSINYA DENGAN PENDIDIKAN AKHLAK DI INDONESIA - Waluyo, Agus; Sani, Mufid Rizal (Jurnal Tawadhu, 2019)
The number of cases of student delinquency lately one of which is due to lack of education and moral habituation to students. Moral education is education about the basics of morals and the virtues of temperament, the character that must be owned and made a habit by children from infancy until he became a Muslim.The Book of Ta'lim Muta'allim by Az-Zarnuji is one of the references in moral education. This book became a tradition in pesantren to be taught, memorized, and internalized to the students. The concept of moral education in the book Ta'lim Muta'allim, among others: 1) the nature of science chapter, 2) chapter intentions in learning, 3) how to choose knowledge, teachers, and friends, 4) glorify science and scholars, 5) seriousness in seeking knowledge, istiqamah and noble ideals, 6) the beginning of learning, the size of learning and order, 7) resignation, 8) time of success, 9) love and advice, 10) use of time, 9) color ', 10 ) strong causes of memorization and causes of forgetfulness, 11) sources and inhibitors of sustenance, as well as increasing and cutting age.The relevance of the concept of morality in the book Ta'lim Muta’allim with moral education in Indonesia, among others; 1) morals to God, 2) morals to oneself, 3) morals to others.